Practical approach to tobacco cessation: A review - Mittal, Sachin; Jain, Vibha; Duvvuru, Lakshmi Sudha Reddy; Rao, Zeba; Khare, Ankita; Gupta, Akash; Gupta, Jitendra Kumar (Journal of Orofacial Research, 2020)
Tobacco use is one of the most important causes of preventable death and disability worldwide. Quitting the habit of tobacco consumption has substantial benefits. Although, nicotine gum was the only Food and Drug Administration approved pharmacotherapy until 1991, however, today, a variety of therapies are available for tobacco cessation. It becomes important that the health care professionals are familiar with the spectrum of therapies so that they can address the needs of tobacco users effectively. Health care professionals can contribute to the health of the community by motivating the tobacco users to quit and assisting them in the process of tobacco cessation. This review discusses the pharmacological and nonpharmacological therapies that have been used for the treatment of tobacco dependence.